THE (UN)SILENT ENEMY: HOW INDONESIAN PUBLIC OPINION IS UNDERMINING NATIONAL DEFENSE - Triantama, Febry; Indradi Abdul, Tafarel Sebrio; Rayasti, Avelitra Fitrianni (Jurnal Dinamika Global, 2024)
The inadequate state of Indonesia's defense posture appears to be an open secret that has been known to the public for decades. Indonesia's weak defense posture is not only caused by the quantity of defense equipment owned, which is not aligned with the needs, but it is also caused by the large number of Indonesian defense equipment aged over 30 years. The fundamental cause of Indonesia's weak defense posture is a lack of adequate defense budget support. Referring to various studies, ideally, Indonesia allocates a defense budget above 1% of GDP. However, Indonesia has stagnantly allocated a defense budget of 0.7%-0.9% of GDP. The breakthrough that the government was trying to make through the discourse on a budget of 1,700 trillion for acquiring defense equipment failed to materialize because it was rejected. Through analysis using theories related to the determinants of the defense budget, this article concludes that the stagnation of the Indonesian defense budget is caused by low public support for increasing the defense budget. Lacking public support has resulted in the government choosing to allocate the funding to other, more populist sectors, such as infrastructure development and well-being. It is also intended that the political elite gain electoral support.